Musculoskeletal Pain and its Ergonomics Risk Factors among School Teachers from Tamil Nadu, India: a Cross-Sectional Study - Gowthaman Sankar; Vijayakrishnan Ganesan; Indraja Katam; K. Bincy (International Journal of Occupational Safety and Health, 2024)
Introduction: Teachers are often exposed to occupational hazards like musculoskeletal pain which may force them to early retirement from their jobs, affecting their quality of life. This study aimed to estimate the prevalence of musculoskeletal pain among government school teachers and to assess its ergonomic risk factors.